Effects of catecholamines on free fatty acid release from bone marrow adipose tissue. - M A Tran; T L Dang; M Berlan (Journal of Lipid Research, 1981)
We have studied the effect of epinephrine and isoproterenol on free fatty acid (FFA) mobilization from bone marrow adipose tissue in dog tibia after constant-flow autoperfusion of the nutrient artery by ipsilateral femoral arterial blood. The perfusions of epinephrine (0.025 microgram/min) or isoproterenol (0.005 microgram/min) significantly increased the FFA level in the nutrient vein of the tibia. Moreover, our data demonstrate that in vitro the bone marrow adipose tissue was less responsive to catecholamines than omental adipose tissue. It can be concluded that bone marrow adipose tissue is able to release FFA after administration of catecholamines but to a lesser extent than in other adipose tissue (omental adipose tissue). These results support the hypothesis that the bone marrow adipose tissue is involved in local nutrition rather than in the total energy supply of the animal.